Improving lung health in low-income and middle-income countries: from challenges to solutions. Issue 10277 (6th March 2021) - Meghji, Jamilah; Mortimer, Kevin; Agusti, Alvar; Allwood, Brian W; Asher, Innes; Bateman, Eric D; Bissell, Karen; Bolton, Charlotte E; Bush, Andrew; Celli, Bartolome; Chiang, Chen-Yuan; Cruz, Alvaro A; et al.
Summary: Low-income and middle-income countries (LMICs) bear a disproportionately high burden of the global morbidity and mortality caused by chronic respiratory diseases (CRDs), including asthma, chronic obstructive pulmonary disease, bronchiectasis, and post-tuberculosis lung disease. CRDs are strongly associated with poverty, infectious diseases, and other non-communicable diseases (NCDs), and contribute to complex multi-morbidity, with major consequences for the lives and livelihoods of those affected. The relevance of CRDs to health and socioeconomic wellbeing is expected to increase in the decades ahead, as life expectancies rise and the competing risks of early childhood mortality and infectious diseases plateau. As such, the World Health Organization has identified the prevention and control of NCDs as an urgent development issue and essential to the achievement of the Sustainable Development Goals by 2030. In this Review, we focus on CRDs in LMICs. We discuss the early life origins of CRDs; challenges in their prevention, diagnosis, and management in LMICs; and pathways to solutions to achieve true universal health coverage.